Selection of White-Rot Fungi for Decolorization of Palm Oil Mill Effluent and Evaluation of Biodegradation and Biosorption Processes - Sanhathai Ridtibud, Nuttika Suwannasai, Apichaya Sawasdee, Verawat Champreda, Cherdchai Phosri, Sarper Sarp, Nipon Pisutpaisal and Siriorn Boonyawanich (Nature Environment and Pollution Technology, 2024)
Ten species of white-rot fungi were evaluated for their ability to decolorization of palm oil mill effluent. The highest decolorization efficiency was found with Trametes elegans (PP17-06), followed by Ganoderma sp.2 (PW17-06) and Ganoderma sp.2 (PW17-177), respectively. T. elegans was further evaluated for the long-term performance of decolorization for 24 d. The optimal retention time for the decolorization was 8 d, with a color removal efficiency of 47.7%. Beyond 18 d of incubation, decolorization efficiency was reduced due to the autolysis of enzymes. During the biodegradation process, manganese peroxidase enzyme activities reached a maximum of 36.03 U.L−1. However, no significant laccase and lignin peroxidase activities were observed. T. elegans was also assessed for decolorization performance through biosorption on mycelial biomass. The synthesis of the enzyme was prevented by exposing the mycelium to HgCl2. Within an optimal contact time of 2 d, decolorization efficiency reached 12.5% with ADMI reduction from 4259.0 (±20.1) ADMI to 3727 (±104.04) ADMI. Results indicate that the adsorption capacity was reached at this time, and no significant color removal can be achieved by biomass. Results obtained in this study showed the potential of T. elegans in decolorizing palm oil mill effluent.